MECANISMOS DE DERRAMAS DE CONOCIMIENTO EN EL CONTEXTO DE LAS RELACIONES ENTRE GRANDES, PEQUEÑAS y MEDIANAS EMPRESAS - Chauca M., Pablo (2019)
The relationships between big companies and the small and mid-size companies (SMEs) are an important and simultaneously controversial subject. With the advances of the globalisation processes, in particular from the economic policies that privilege the commercial opening, it is emphasized in the positive impacts of the direct foreign investment in the economic dynamics of the receiving countries. In that context, diverse studies focus to the analysis of the spillover of big companies (transnational and national) towards local SMEs and suppose that the increases of productivity of these last ones are related to the spillover knowledge from the big ones. Other investigations emphasize the asymmetric relations between the big companies and the SMEs, for such reason maintain that the impacts are more negative on the smaller companies and significantly does not exist technological and productive accumulation of learnings, abilities and capacities in the SMEs. Having as frame the debate from these studies, the work analyze which are the advantages and the difficulties that the SMEs face for the advantage of the spillover knowledge as well as which are the specific mechanisms for their accumulation. In order to illustrate the argumentations the experience in some mexican industries is taken like reference.